Traffic flow and transportation - Newell, Gordon F. (New York ; London : American Elsevier Pub. Co., 1972)
This volume is the fifth in a series of international symposia on the theory of traffic flow and transportation.
Proceedings of the fifth international symposium on the theory of traffic flow and transportation held at Berkeley, California, June 16-18, 1971.
Sponsors: National Science Foundation, Mathematical and Physical Sciences Division, and others.
Includes bibliographical references.
ne 24/01/2019
Loans
Keywords: Traffic flow; Traffic engineering